Comparative neuroprotective effects of Cerebrolysin, dexamethasone, and ascorbic acid on sciatic nerve injury model: Behavioral and histopathological study - Elhessy, Heba M.; Habotta, Ola A.; Eldesoqui, Mamdouh; Elsaed, Wael M.; Soliman, Mona F. M.; Sewilam, Haitham M.; Elhassan, Y. H.; Lashine, Nermeen H. (Frontiers in Neuroanatomy, 2023)
Background The majority of the suggested experimental modalities for peripheral nerve injury (PNI) result in varying degrees of recovery in animal models; however, there are not many reliable clinical pharmacological treatment models available. To alleviate PNI complications, research on approaches to accelerate peripheral nerve regeneration is encouraged. Cerebrolysin, dexamethasone, and ascorbic acid (vitamin C) drug models were selected in our study because of their reported curative effects of different mechanisms of action. Methodology A total of 40 adult male albino rats were used in this study. Sciatic nerve crush injury was induced in 32 rats, which were divided equally into four groups (model, Cerebrolysin, dexamethasone, and vitamin C groups) and compared to the sham group (n = 8). The sciatic nerve sensory and motor function regeneration after crushing together with gastrocnemius muscle histopathological changes were evaluated by the sciatic function index, the hot plate test, gastrocnemius muscle mass ratio, and immune expression of S100 and apoptosis cascade (BAX, BCL2, and BAX/BCL2 ratio). Results Significant improvement of the behavioral status and histopathological assessment scores occurred after the use of Cerebrolysin (as a neurotrophic factor), dexamethasone (as an anti-inflammatory), and vitamin C (as an antioxidant). Despite these seemingly concomitant, robust behavioral and pathological changes, vitamin C appeared to have the best results among the three main outcome measures. There was a positive correlation between motor and sensory improvement and also between behavioral and histopathological changes, boosting the effectiveness, and implication of the sciatic function index as a mirror for changes occurring on the tissue level. Conclusion Vitamin C is a promising therapeutic in the treatment of PNI. The sciatic function index (SFI) test is a reliable accurate method for assessing sciatic nerve integrity after both partial disruption and regrowth.